Chemical composition, antioxidant, antimicrobial and anti-inflammatory activity of Prunus spinosa L. fruit ethanol extract. (April 2020) - Sabatini, Luigia; Fraternale, Daniele; Di Giacomo, Barbara; Mari, Michele; Albertini, Maria Cristina; Gordillo, Belén; Rocchi, Marco Bruno Luigi; Sisti, Davide; Coppari, Sofia; Semprucci, Federica; Guidi, Loretta; Colomba, Mariastella
Graphical abstract: Highlights: P. spinosa fruit extract shows a wide antibacterial activity and yeast inhibition. P. spinosa fruit extract shows antioxidant properties, mostly due to anthocyanins. P. spinosa extract modulates miR-126 and miR-146a leading anti-inflammatory effects. P. spinosa extract shows a high potential as a source of functional additives. We suggest using the extract for preparation of new foods beneficial for consumers. Abstract: Prunus spinosa L. (from Italy) fruit ethanol extract (40 µg/mL) was assessed by evaluating the antioxidant, anti-inflammatory and antimicrobial activities against five bacterial and two fungi ATCC strains. Moreover, the phenolic profile was also investigated and results are indicative of an intense anthocyanin accumulation which may be responsible for the antioxidant properties revealed by the DPPH assay. MIC and MBC/MFC values (4.36–8.72 mg/mL; 8.72–17.44 mg/mL, respectively) revealed a wide antibacterial activity and yeast inhibition. No specific inhibitory action was observed against the tested Gram-negative or Gram-positive bacteria. Preliminary data on the effect on both miR-126 and miR-146a expression levels suggested a very interesting anti-inflammatory activity of the extract. A possible mechanism underpinning the observed effects was hypothesized and discussed. Finally, P. spinosa fruit extract could be used as supplementary source of functional additives and might be a promising antimicrobial compound of natural origin to be employed to fight microbial resistance.